University proceedings. Volga region. Social sciences - R.S. Markunin (Известия высших учебных заведений. Поволжский регион: Общественные науки)
Background. A number of reasons can lead to the emergence of legal anomie as a crisis state of society, among which the excessive regulation of social relations should be highlighted. In this connection, it is necessary to develop a method of countering the regi-mentation of public life, and at the same time to propose means to combat manifestations of legal anomie. The purpose of the work is to substantiate the need for a process of reforming the current legislation aimed at overcoming legal anomy in relations between the state and society. Materials and methods. Various scientific works devoted to revealing the charac-teristic features of social and legal anomie were used. The current legislation was also ana-lyzed for the presence of regulated social relations. The main methodological method was the dialectical method of cognition. Methods were also used: formal legal, logical, compar-ative. Results. The relationship between the above paired categories has been established, which manifests itself in the possibility of transition from one state to another. The problem of the presence in the current legal system of ineffective regulation of social relations in the sphere of functioning of the state apparatus, which also leads to an increase in the legal anomy of officials and the mechanism of the state as a whole, is identified. The conse-quences of the excessive regulation of social relations are demonstrated using the example of the implementation of the institution of tax deduction. The importance of a balanced approach to the issue of excessive regulation of social relations is shown using the example of currently existing methods of legal regulation of the banking sector and entrepreneur-ship. Conclusions. The study of the problem of excessive regulation of social relations led to the conclusion about the need to constantly search for effective methods of combating manifestations of legal anomie in order to maintain a high performance indicator of the entire legal system of society.